Kunsten at lede primadonnaer: Når god ledelse spænder ben for kunsten - Hedegaard Hein, Helle (Peripeti, 2009)
Danish theatres are experiencing a leadership gap: Leadership competencies are in sore need of an upgrade, but the existing body of knowledge in terms of artists’ motivational profile is insufficient. This article presents a model of four archetypes of artists, each having their own motivational profile and leadership need, and discusses the implications for leadership in theatres. One major implication is that effective leadership must be based on politically incorrect leadership principles.